The Complete Mitochondrial Genome of Eurasian Minnow (Phoxinus cf. Phoxinus) from the Heilongjiang River, and Its Phylogenetic Implications - Lei Cheng; Ezhou Wang; Weitao Li; Xiaoli Yu; Xiaolin Liao (Animals, 2022)
Over the past two decades, the genus Phoxinus has undergone extensive taxonomic revision and many new species or mitochondrial lineages have been found in Europe. However, Asian populations of Phoxinus spp. have received less attention and have rarely been compared with their European relatives. In this study, we deciphered the 16,789-nucleotide mitochondrial genome of Phoxinus cf. phoxinus from the Heilongjiang River (HLJ) and compared it with other known mitogenomes or partial mitochondrial DNA (mtDNA) sequences of Phoxinus spp. We discovered that all known mitochondrial genomes of Phoxinus had a typical mtDNA architecture across vertebrates, but their D-loop regions varied greatly in length. A repetitive motif of ~130 bp was identified in the D-loop regions of Phoxinus spp. The unusual repetitive structure was revealed at the beginning of D-loop regions of all known mitogenomes of Phoxinus spp. The length differences of the D-loop region were attributed mainly to the number of repetitive motifs and the inserted sequences among them. However, this repetitive structure was absent in the other Far East phoxinins. This is further evidence for the notion that Far Eastern phoxinins should be divided into two genera: Phoxinus and Rhynchocypris. All mtDNA sequences (including three mitogenomes) from South Korea represent the same genetic lineage, as there were only slight differences among them. The remaining six mtDNA sequences are highly divergent and represent different lineages of the genus, as supported by partial mtDNA sequences. The updated phylogeny of genus Phoxinus suggests that there are five distinct mtDNA lineages in Asia. The Asian lineages have diverged markedly from their European relatives and should not be included with the European minnow (P. phoxinus).